HIV-ASSOCIATED VENOUS THROMBOEMBOLISM - Michele Bibas; Gianluigi Biava; Andrea Antinori (Mediterranean Journal of Hematology and Infectious Diseases)
<!--[if gte mso 9]> Normal 0 14 false false false IT X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> HIV infection has been recognized as a prothrombotic condition and this association has now been proven by a large number of studies with a reported VTE frequency among HIV-infected patients ranging from 0.19% to 7,63 %/year. HIV infection is associated with a two to tenfold increased risk of venous thrombosis in comparison with a general population of the same age. Some risk factors demonstrated a strongest association with VTE such as, low CD4+ cell count especially in the presence of clinical AIDS, protein S deficiency, and protein C deficiency. Whereas other risk factors are still controversial like protease inhibitor therapy, presence of active opportunistic infections and presence of antiphospholipid antibodies, including anticardiolipin antibodies and lupus anticoagulant. Physicians caring for HIV positive patients should be able to recognize and treat not only the well-known opportunistic infections and malignancies associated with this chronic disease, but also be alert to the less well-known complications such as thromboses. Pulmonary embolism should be included in the differential diagnosis when patients with HIV/AIDS have unexplained dyspnea or hypoxemia. In younger individuals with VTE, especially men, without other identifiable risk factors for VTE, HIV should be considered. Because interactions between warfarin and antiretrovirals is possible, health care providers should also be alert to the potential of dangerously high or low INRs when they are giving anticoagulants to patients with HIV infection who are undergoing antiretroviral therapy.